Penegasan Ḥifd} Al-‘Alam Sebagai Bagian Dari Maqāṣhid Al-Sharī’ah - Suryani Suryani (AL-TAHRIR, 2017)
Abstract: Environmental damage is not something new and becomes people’s concern in this recent global era. Many data show that environmental ecosystems have started to damage due to the humans’actions themselves. Islam with its various sciences is required to be able to instill the people’s awareness to keep, maintain, and conserve the environment from destruction, pollution and over-exploitation. Islam must be able to instill the awareness to all people that environment is one important ecosystem for human life to survive. However, these beliefs are still less satisfactorily explored by the Islamic literature treasures. Thus, the author attempts to present an environmental conservation to become one important life issue for today. This theological awareness should be well developed using the theory of Maqāṣid al-Sharī’ah which has been widely discussed in Islamic literature. If the soul keeping (hifz} al-nafs) has previously become a fundamental problem in fiqh, the environmental keeping (hifz} al-’alam) should also become one accountable aspect for today due to the humans’ important relationship with the environment where they live. This awareness is also intended to build a good relationship between humans and their surrounding environmental ecosystems.